Morphological characters and molecular data reveal a new species of Rhodonia (Polyporales, Basidiomycota) from China - Yuan, Yuan; Shen, Lu-Lu (Phytotaxa, 2017)
A new polypore, Rhodonia tianshanensis, collected from West Tianshan Nature Reserve in Xinjiang Autonomous Region (northwest China), is described and illustrated based on morphological characteristics and molecular evidence. It is characterized by having resupinate basidiomata with an oblique tube layer, fusoid cystidioles in the hymenium, and cylindrical basidiospores. Based on multiple loci DNA sequences including the internal transcribed spacer (ITS), the large subunit (nLSU), and the second subunit of RNA polymerase II (RPB2) regions, our phylogeny strongly supported R. tianshanensis as a new species belonging to the genus Rhodonia.